2018
DOI: 10.4103/picr.picr_86_17
|View full text |Cite
|
Sign up to set email alerts
|

Drug prescription pattern of outpatients in a tertiary care teaching hospital in Tamil Nadu

Abstract: Purpose:Drug use prescribing indicators advocated by the World Health Organization (WHO) are important tools for assessing the degree of polypharmacy, use of generic medicines, and to evaluate if there is inappropriate use of antibiotics or parenteral medications besides estimating the adherence to the essential drugs list. This study aimed to assess the WHO prescribing indicators in prescriptions given at the medical outpatient department (OPD) in a private medical college hospital in South India.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
(20 reference statements)
3
11
3
Order By: Relevance
“…Ahmed et al [13] reported that quinolones group was prescribed in 9.1% of the outpatient antibiotics prescriptions. In contrast to our study, Shanmugapriya et al [14] stated that the highest prescribed antibiotic was levofloxacin followed by co-trimoxazole. Shapiro et al [15] reported that the majority of antibiotics prescribed for adults in ambulatory care settings are broad-spectrum agents, most commonly fluoroquinolones and macrolides.…”
Section: Discussioncontrasting
confidence: 99%
“…Ahmed et al [13] reported that quinolones group was prescribed in 9.1% of the outpatient antibiotics prescriptions. In contrast to our study, Shanmugapriya et al [14] stated that the highest prescribed antibiotic was levofloxacin followed by co-trimoxazole. Shapiro et al [15] reported that the majority of antibiotics prescribed for adults in ambulatory care settings are broad-spectrum agents, most commonly fluoroquinolones and macrolides.…”
Section: Discussioncontrasting
confidence: 99%
“…11,12 Being trivial errors they are unlikely to hamper dispensing of the correct drug, however mentioning them, shall help the pharmacist to correlate and interpret the correct drug, formulation and dose, especially among the handwritten prescriptions. 13 Use of brand names in the current study was very high similar to the study by Shanmugapriya et al 14 Extensive use of brand names by the prescribing physician, can contribute to prescription errors. In our tertiary care setting where a single pharmacy dispenses drug of various specialties, errors can be common.…”
Section: Discussionsupporting
confidence: 79%
“…9 The probable description for the low percentage of generic prescribing could be owing to frequent and influential encouragement of the propriety products by pharmaceutical companies and in certain case, clinicians are bound to concede to the resolve of wealthy patients demanding pacesetter drugs for treatment. 3 In the present study 11.93% of encounters had an injection prescribed which is somewhat higher than Bhatnagar et al (10%) but lower than the study carry out (14%) and another study conducted by Simpson et al reported 38% and Mittal et al 80% use of injectables. [10][11][12] Injectable drugs are connected with trouble of administration and medication errors.…”
Section: Discussioncontrasting
confidence: 56%
“…However, irrational drug use, considered as a universal risk is mainly common in the developing countries due to irrational prescribing, stipulation, and management of medications. 2,3 Medical prescription is a significant document of medico legal value too, that can be kept as proof in medico legal cases in court of law and thus should be cautiously and critically considered. More than 50% of all medicines global are prescribed, dispensed, or sold improperly and 50% of patients not succeed to take them perfectly.…”
Section: Introductionmentioning
confidence: 99%